The influence of the diamond passing exercise modelnand triangle against passing accuracy football on extracurriculars - Nurwahidin Hakim; Juli Candra; Andi Amry Yahya; Irsan Kahar (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2022)
Abstract This study aims to determine the effect of diamond passing and passing triangle training models on football passing accuracy in SMP Negeri 8 Palopo football extracurriculars. This research is a type of Quantitative research. The population and sample of this study were extracurricular participants in SMP Negeri 8 Palopo, which numbered 20 students. The research design used is One group pretest-posttest design. What is given is diamond passing and passing triangle training. The data obtained is processed using SPSS version 26.0. The results of the t-test of experimental group 1 can be seen t count > t table: 8,189 > 2,306 with a significance of 0.000 < 0.05. in experimental group 2 can be seen t count > t table:7,875 > 2,306 with a significance of 0.000 < 0.05. So, this result shows that there is a significant difference. From the results of the pre-test and post-test comparison test of experimental group I and experiment group II, it is known that the passing diamond > passing triangle: 8,189 > 7,875. Thus, it can be concluded that "There is an influence of the diamond passing training model on passing accuracy in football extracurriculars